Antonyms in “Johnson Dictionary” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the composition of normative-explanatory dictionaries, and in particular, the interpretation of antonyms in the Johnson dictionary, from the perspective of modern lexicography. The article notes the existence of various vocabulary groups included in the dictionary in lexicography. Also, the issue of inclusion of normative lexicon and non-normative lexicon in the dictionary is discussed.